Halal Certification Priorities for Indonesian MSEs: A Comparison Between Stakeholder Perspectives and AI-Based Insights - Anita Priantina; Safeza Mohd Sapian; Zurina Shafii; Norhazlina Ibrahim (Islamic Economics Study Program, Muhammadiyyah University of Makassar, 2026)
Non-Indexed Publication